Los monólogos de la vagina y Hombres en escabeche: reescritura de la sexualidad femenina como una liberación de los tabúes patriarcales que han mantenido a la mujer subyugada - Acón Chan, Lai Sai (2004)
This is the last of three articles, all of which stemmed from The Process of Female Subject Formation Through Her Sexual Identity, a research project sponsored by the Program of Gender and Identity Issues from the CIICLA, an acronym in Spanish for Center of Research on Latin American Identity, a research center from the University of Costa Rica. This study is meant to analyze the Vagina Monologues and Hombres en escabeche with feminist psychoanalytical theories by Julia Kristeva, Luce Irigaray y Hélène Cixous in order to provide women with a voice.